DIGITALISASI TATA RUANG DESA MIMBALA UNTUK PEMETAAN WILAYAH YANG MENDUKUNG INFRASTRUKTUR BERKELANJUTAN - Andini Aminarsi; Dwi Purnomo; Putri Nur Sakinah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
This community service activity aims to assist the Mimbala Village government in compiling digital-based village spatial data as a reference for targeted and sustainable infrastructure planning and development. The main problem faced is the unavailability of accurate and standardized regional maps, so the development planning process is often not based on valid data. The activity methods include field surveys and digital map creation using a Geographic Information System (GIS)-based mapping application. The legal basis for implementing this activity refers to Law Number 6 of 2014 concerning Villages, Regulation of the Minister of Villages, Disadvantaged Regions, and Transmigration Number 21 of 2020 concerning General Guidelines for Village Development and Village Community Empowerment, and Regulation of the BIG Number 3 of 2016 concerning Guidelines for Mapping Village Administrative Areas. The result of the activity is a digital map of the Mimbala Village area that includes administrative boundaries, road networks, public facilities, and potential land for development. This map is a strategic tool for the village government to compile spatial data-based development plans, improve decision-making accuracy, and support transparency and accountability in village development management. Thus, this community service strengthens village governance and encourages sustainable development based on digital mapping.